HLA II class antigens and susceptibility to coeliac disease - Vojvodic, Svetlana; Ademovic-Sazdanic, Dusica (Genetika (Beograd), 2011)
Coeliac disease (CD) is a systemic autoimmune, complex and multifactorial disorder, which is caused by interactions between genetic and environmental factors. The only established genetic risk factors so far are the human leucocyte antigens. The aim of this study was to assess the distribution of II class human leukocyte antigens (HLA) in patients with coeliac disease and to investigate the susceptibility to coeliac disease in family members. We typed HLA DR and DQ antigens in 37 patients from Vojvodina with coeliac disease, 23 first-degree relatives, and 210 controls, serologically using standard lymphocytotoxicity technique. HLA DQ5(1), DQ6(1), DR11(5), DQ7(3), DQ2 and DR15(2) were the most common antigens in the control group. Frequency of HLA DQ2, DR3 and DR7 was higher in CD patients than in the control group. The relative risks for HLA DQ2, DR3 and DR7 were 4.846, 6.986 and 2.106, respectively, while positive association was found between HLA DQ2 and DR3 and CD. Frequency of HLA DQ2, DR3 and DR16(2) was higher in first-degree relatives than in the control group while a positive association was found between HLA DQ2 and DR3. A negative association was found between HLA DQ5(1) and DQ6(1) in coeliac patients from Vojvodina and their relatives, in addition to HLA DR11(5) in the group of relatives (RR=0.363,PF=0.232). These findings indicate the impact of the HLA testing for CD in clinical practice in order to rule out the possibility to CD in doubtful cases or in at-risk subjects. Celijakija je sistemski autoimuni, kompleksni i multifaktorijalno uzrokovan poremecaj koji nastaje kao posledica interakcije genetskih i ekoloskih faktora. Jedini potvrdjeni genetski faktori rizika za sada su humani lukocitni antigeni. Cilj ovog rada je bio da se proceni distribucija II klase humanih leukocitnih antigena (HLA) kod bolesnika sa celijakijom i da ispita predispozicija za nastanak celijakije u clanove njihovih porodica. Vrsena je tipizacija HLA antigena DR i DQ lokusa kod 37 pacijenata iz Vojvodine obolelih od celijakije, 23 osobe u prvom stepenu srodstva kao i kod 210 zdrave osoba, seroloski standardnim mikrolimfocitotoksicnim testom. HLA DQ5(1), DQ6(1), DR11(5), DQ7(3), DQ2 i DR15 (2) su najcesce zastupljeni antigeni u kontrolnoj grupi. Ucestalost HLA DQ2, DR3 i DR7 je bila veca u bolesnika sa celijakijom nego u kontrolnoj grupi. Relativni rizik za HLA DQ2, DR3 i DR7 iznosi 4.846, 6.986 i 2.106, dok je pozitivna udruzenost uocena izmedju HLA DQ2 i DR3 i celijakije. Ucestalost HLA DQ2, DR3 i DR16(2) bila je veca u osoba u prvom stepenu srodstva sa obolelim od celijakije nego u kontrolnoj grupi, dok je pozitivna asocijacija uocena izmedju HLA DQ2 i DR3. Negativne asocijacije su uocene izmedju HLA DQ5(1) i DQ6(1) i bolesnika sa celijakijom sa teritorije Vojvodine i njihovih srodnika, kao i HLA DR11(5) u grupi srodnika (RR = 0.363, RF = 0.232). Ovi nalazi ukazuju na znacaj testiranja HLA antigena i njenu primenu u klinickoj praksi kod osoba sa ispoljenim simptomima bolesti kao i mogucnost utvrdjivanja rizika za nastanak bolesti kod clanova njihovih familija.